2015
DOI: 10.1007/s11999-014-3855-8
|View full text |Cite
|
Sign up to set email alerts
|

Does HIV Infection Increase the Risk of Perioperative Complications After THA? A Nationwide Database Study

Abstract: Background Recent studies have shown successful mid-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 18 publications
0
37
1
3
Order By: Relevance
“…Among patients with well-managed HIV and no concurrent diagnosis of hemophilia, the authors of the current study found no decrease in survivorship or increase in complications at a mean followup of 6 years. This is in contrast to a number of earlier studies [4,5,7,9] examining joint arthroplasty in patients with HIV, which suggested a greater risk of complications and poorer implant survival in this patient group.…”
contrasting
confidence: 99%
“…Among patients with well-managed HIV and no concurrent diagnosis of hemophilia, the authors of the current study found no decrease in survivorship or increase in complications at a mean followup of 6 years. This is in contrast to a number of earlier studies [4,5,7,9] examining joint arthroplasty in patients with HIV, which suggested a greater risk of complications and poorer implant survival in this patient group.…”
contrasting
confidence: 99%
“…We suspect that factors inherent to their HIV‐status, like risk of infections and medications used, along perhaps with social factors could contribute to these findings. Increased LOS has been noted previously following other procedures in HIV‐infected individuals . However, a recent analysis by Robich et al using data from the NIS dataset found no differences in LOS or hospitalization cost following cardiac surgery in HIV‐infected individuals when compared to non‐infected individuals …”
Section: Discussionmentioning
confidence: 99%
“…1 A Kaplan-Meier survivorship curve for the HIV (red) and control (blue) cohorts up to 10 years is shown when considering TKA. Some studies have suggested that patients with HIV may have a higher risk of complications after undergoing a TKA [11,12] and less satisfactory implant survival [11,15,17], however, a recent database study showed no significant differences in overall perioperative complications [5]. Therefore, we aimed to determine if patients with HIV had comparable clinical outcomes and complication rates as matched counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is great concern that these patients may be at greater risk when they undergo any elective surgical procedures, including lower extremity total joint arthroplasty [12,14]. Numerous studies have reported a higher risk of perioperative complications including myocardial infarction, acute renal failure, and surgical site infection [6,[11][12][13]15]. Furthermore, some studies have reported lower implant survivorship after total joint arthroplasty in patients with HIV compared with those without the virus [17,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation